2019
DOI: 10.1007/s00027-019-0665-9
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide emission from drawdown areas of a Brazilian reservoir is linked to surrounding land cover

Abstract: Reservoir sediments exposed to air due to water level fluctuations are strong sources of atmospheric carbon dioxide (CO 2). The spatial variability of CO 2 fluxes from these drawdown areas are still poorly understood. In a reservoir in southeastern Brazil, we investigated whether CO 2 emissions from drawdown areas vary as a function of neighboring land cover types and assessed the magnitude of CO 2 fluxes from drawdown areas in relation to nearby water surface. Exposed sediments near forestland (average = 2733… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…The incidence of extreme droughts decreases reservoir water levels, exposing large areas of previously submerged aquatic sediment to direct contact with the atmosphere. Exposed aquatic sediments have been reported as significant sources of greenhouse gases (GHG) to the atmosphere, especially carbon dioxide (CO 2 ) and methane (CH 4 ) [21][22][23][24]. However, when precipitation levels return to normal and the reservoir water level rises, these exposed sediments become submerged again.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of extreme droughts decreases reservoir water levels, exposing large areas of previously submerged aquatic sediment to direct contact with the atmosphere. Exposed aquatic sediments have been reported as significant sources of greenhouse gases (GHG) to the atmosphere, especially carbon dioxide (CO 2 ) and methane (CH 4 ) [21][22][23][24]. However, when precipitation levels return to normal and the reservoir water level rises, these exposed sediments become submerged again.…”
Section: Introductionmentioning
confidence: 99%
“…Mean CO 2 efflux from El Gergal reservoir drawdown area exposed sediments was on average ~ 70 times higher than the mean annual CO 2 emissions from the reservoir surface at lacustrine zone (~ 5.4 mg m -2 h -1 , Montes-Pérez et al, 2022), revealing that El Gergal drawdown area constitutes a relevant CO 2 emission hotspot. In agreement, a review by Almeida et al (2019) suggested that the average CO 2 flux from global exposed sediments (considering very different aquatic ecosystems, such as reservoirs, temporary ponds, temporary streams and rivers) is roughly one order of magnitude higher than the average of CO 2 flux from global reservoir surfaces.…”
Section: Resultsmentioning
confidence: 63%
“…Interestingly, it also resembles the range of CO 2 efflux from Mediterranean soils (Bond-Lamberty & Thomson, 2010;Von Schiller et al, 2014;Gómez-Gener et al, 2015). However, despite high respiration rates, terrestrial soils use to be carbon sinks due to elevated primary production of overlying vegetation, while dry exposed sediments of reservoir ecosystems frequently lack primary producers to compensate for CO 2 production, and constitute CO 2 sources (Almeida et al, 2019).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…With the global need for energy growing, extensive hydroelectricity expansion is currently underway 4 . Construction of reservoirs and dams is, however, associated with substantial environmental costs, such as biodiversity loss 5,6 , fish migration 5 , increased emissions of greenhouse gases 7,8 , and the potential for increased contaminant exposure, including exposure to mercury (Hg) [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%